2013
DOI: 10.1093/tropej/fmt013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Children with Bacterial Meningitis

Abstract: Bacterial meningitis is a common cause of morbidity and mortality in children. The oxidative stress in bacterial meningitis is barely determined. Forty children with bacterial meningitis were studied for their oxidants and antioxidants status in serum and cerebrospinal fluid. Fever (95%) was commonest presentation followed by seizure and vomiting. Neck rigidity and Kernig's sign were present in 37.5% and 27.5% cases, respectively. Plasma and cerebrospinal fluid malondialdehyde, protein carbonyl and nitrite lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In our previous studies, we showed that increased oxidative stress is related to increased inflammatory cytokines, Helicobacter infection, and bacterial meningitis [22, 23]. In present study it is shown that SPA, TOS, and OSI were significantly increased and TAS was significantly decreased in patients with T2DM, DN, and ESRD than healthy subjects.…”
Section: Discussionsupporting
confidence: 60%
“…In our previous studies, we showed that increased oxidative stress is related to increased inflammatory cytokines, Helicobacter infection, and bacterial meningitis [22, 23]. In present study it is shown that SPA, TOS, and OSI were significantly increased and TAS was significantly decreased in patients with T2DM, DN, and ESRD than healthy subjects.…”
Section: Discussionsupporting
confidence: 60%
“…A decrease in enzymatic defense, such as SOD and CAT levels, was observed in both the PFC and hippocampus of the meningitis rats. Srivastava et al have reported clinical evidence for an increase in MDA, protein carbonyl, and nitrite levels and a decrease in enzymatic defense levels in the plasma and CSF of meningitis patients [48]. We also measured mitochondrial complex I, II, III, and IV activity in the PFC and hippocampus, and in the 24-h group, we found a decrease in complex III activity in the meningitis group compared to that in the control group (data not shown).…”
Section: Discussionmentioning
confidence: 56%
“…In many CNS diseases, such as traumatic brain injury (TBI), stroke, hydrocephalus, and post-hemorrhagic and post-ischemic brain damage, lipid peroxidation has been demonstrated to play a key role in brain damage [11]. Even CNS infection pathophysiology has been demonstrated to involve oxidative stress [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have interestingly shown that brain-specific increase in lipid peroxidationevaluated into the CSF through serial sampling-exists soon after surgical injury, since no significant MDA or ascorbate variations exist in systemic plasma samples obtained by contemporary collection despite a marked postoperative inflammatory response (witnessed by IL-6 and IL-8 plasma levels increase). The issue of brain-limited oxidative event has been debated in comparison with the available literature: In our opinion, an extensive BBB breakage is only present in severely inflamed brain, as in meningitis-meningoencephalitis patients [12,13]. Therefore, most papers dealing with MDA increase in plasma refer to diffusely involved endothelium.…”
Section: Discussionmentioning
confidence: 99%